Development of Problem Based Learning Based E-modules in the form of Flipbooks on Environmentally Friendly Technology Materials As an Independent Learning Material for Students Especially Online Learning - Munzil Munzil*; Yessi Affriyenni; Siti Mualifah; Indra Fardhani; Isnanik Juni Fitriyah; Muntholib Muntholib (Jurnal Pendidikan Sains Indonesia, 2022)
Problem solving skills are important to have in the 21st century. In the online learning period, students are required to be able to learn independently from home. However, in fact the motivation of students' learning has decreased. To facilitate students' self-learning during online learning, improving learning motivation and problem solving skills, teachers need to provide interesting learning materials. Therefore, this research aims to develop self-learning materials in the form of problem based learning e-module flipbooks on Environmentally Friendly Technology materials. This research is research and development with Lee Owens development model namely analysis, design, development and evaluation. The data collected in the form of qualitative data in the form of comments and suggestions validators and quantitative data in the form of validation scores of material experts, media and readability. The data collection instruments used are material expert validation test sheets, media experts, teachers and readability tests. Data analysis techniques are descriptive analysis. The results showed that the e-module flipbook developed has a succession of feasibility percentages from the validation tests of material experts, media experts and teachers, namely 84.03, 84.62 and 95.00%. Meanwhile, the percentage of readability tests to students was 87.81%. Teachers and students showed a response that the developed flipbook was interesting and suitable for self-learning during the pandemic. It can be concluded that, the e-module flipbook developed falls into the category of very valid (worth using) and excellent. It is expected to test the effectiveness of flipbooks to learning and develop flipbooks for other materials